Efficacy of pp65‐specific TCR‐T cell therapy in treating cytomegalovirus infection after hematopoietic stem cell transplantation. Issue 11 (22nd September 2022) - Liu, Guangna; Chen, Hua; Cao, Xingyu; Jia, Lemei; Rui, Wei; Zheng, Hongli; Huang, Daosheng; Liu, Fang; Liu, Yue; Zhao, Xueqiang; Lu, Peihua; Lin, Xin
Abstract: Cytomegalovirus (CMV) infection remains a major cause of mortality after hematopoietic stem cell transplantation (HSCT). Current treatments, including antiviral drugs and adoptive cell therapy with CMV‐specific cytotoxic T lymphocytes (CTLs), only show limited benefits in patients. T‐cell receptor (TCR)‐T cell therapy offers a promising option to treat CMV infections. Here, using tetramer‐based screening and single‐cell TCR cloning technologies, we identified various CMV antigen‐specific TCRs from healthy donors, and generated TCR‐T cells targeting multiple pp65 epitopes corresponding to three major HLA‐A alleles. The TCR‐T cells showed efficient cytotoxicity toward epitope‐expressing target cells in vitro. After transfer into immune‐deficient mice bearing pp65 + HLA + tumor cells, TCR‐T cells induced dramatic tumor regression and exhibited long‐term persistence. In a phase I clinical trial (NCT04153279), CMV TCR‐T cells were applied to treat patients with CMV reactivation after HSCT. Except one patient who withdrew at early treatment stage, all other six patients were well‐tolerated and achieved complete response (CR), no more than grade 2 cytokine release syndrome (CRS) and other adverse events were observed. CMV TCR‐T cells persisted up to 3 months. Among them, two patients have survived for more than 1 year. This study demonstrates the great potential in the treatment and prevention of CMV infection following HSCT or other organ transplantation. Abstract :